2022
DOI: 10.31219/osf.io/8ux9a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virtual Nature and Psychological Outcomes: A Systematic Review

Abstract: Evidence on the benefits of virtual nature for individuals is steadily increasing. In this contribution, report a systematic review summarizing studies that examined the implications of virtual nature on psychological and psychophysiological outcomes up to 2021. We used Scopus, Web of Science, and PsycINFO to identify the studies of interest. We found 160 records, of which 38 met the eligibility criteria. Results from quality assessment showed that most studies (thirty) were of medium or high quality and only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Future efforts should be directed to replicate these results in other populations and more balanced samples by gender to allow the generalizability of the findings. Second, as recently highlighted 6 , short-term outcomes of VR are promising but future research should also address whether the changes observed hold in the long term, to enlarge the potential implications for interventions. In this regard, it could be important to examine not just the role of cognitive reappraisal in boosting post-exposure subjective vitality but also in sustaining it over time (e.g., after hours, days, weeks).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Future efforts should be directed to replicate these results in other populations and more balanced samples by gender to allow the generalizability of the findings. Second, as recently highlighted 6 , short-term outcomes of VR are promising but future research should also address whether the changes observed hold in the long term, to enlarge the potential implications for interventions. In this regard, it could be important to examine not just the role of cognitive reappraisal in boosting post-exposure subjective vitality but also in sustaining it over time (e.g., after hours, days, weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, compared to previous studies on virtual nature 6 , our study has some important strengths such as a relatively large sample size, a methodological approach that controlled for different possible confounding variables found in the literature, the comparison between different natural environments that includes an under-investigated environment such as the arctic environment, and a focus on the moderators behind virtual nature benefits. To our knowledge, this is the first study to integrate all these features in one study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations